2008
DOI: 10.3201/eid1406.071008
|View full text |Cite
|
Sign up to set email alerts
|

Population-Attributable Risk Estimates for Risk Factors Associated withCampylobacterInfection, Australia

Abstract: multicenter, prospective case-control study involving 1,714 participants >5 years of age was conducted in Australia to identify risk factors for Campylobacter infection. Adjusted population-attributable risks (PARs) were derived for each independent risk factor contained within the fi nal multivariable logistic regression model. Estimated PARs were combined with adjusted (for the >5 years of age eligibility criterion) notifi able disease surveillance data to estimate annual Australian Campylobacter case number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 23 publications
6
102
0
6
Order By: Relevance
“…8 to 29 . 3 % [13,15,38,39]. Recent source attribution studies based on the multilocus sequence typing method (MLST) from England, Scotland and New Zealand estimated that 50-80 % of human cases were related to the chicken reservoir [37,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…8 to 29 . 3 % [13,15,38,39]. Recent source attribution studies based on the multilocus sequence typing method (MLST) from England, Scotland and New Zealand estimated that 50-80 % of human cases were related to the chicken reservoir [37,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Although the adjusted odds ratio (AOR) for cooked chicken was lower than that for undercooked chicken, the higher population-attributable risk (PAR) was explained by a higher proportion of exposed case-patients (74.3% reported eating cooked chicken) (Stafford 2008).…”
Section: Raw or Undercooked Chickenmentioning
confidence: 99%
“…In general, insufficient temperatures and cooking times as well as cross-contamination lead to Campylobacter exposure and thus increased risk of infection. In a multicenter, prospective case-control study conducted by Stafford et al (2008) reported that preventing cross-contamination through washing the cutting board after use with raw chicken (mOR, 0.5; 95% CI, 0.3-0.7) and washing hands after handling raw chicken (mOR, 0.5; 95% CI, 0.4-0.6), were practices associated with a reduced risk of campylobacteriosis .…”
Section: Food Preparation Practicesmentioning
confidence: 99%
“…Na Austrália, a estimativa é de que ocorram mais de 200.000 casos anualmente (Stafford et al, 2008) e os gastos com infecções entéricas excedem 1,2 bilhões de dólares anualmente (Abelson et al,2006).…”
Section: Epidemiologiaunclassified
“…O Campylobacter é a causa mais comum de doença bacteriana veiculada por alimento na Europa, Estados Unidos e alguns outros locais do mundo (Stafford et al, 2008;EFSA, 2015;CDC, 2015) representando um enorme desafio para a saúde e um elevado impacto socioeconômico. Entretanto, reconhecimento do patógeno nas doenças gastrointestinais é dificultado tanto pelas condições de crescimento do microrganismo como pela subnotifição da doença (Jore et al, 2010;Havelaar et al, 2013;EFSA, 2015).…”
Section: Relevância Do Estudounclassified